Archiving challenges and public history: Exhibiting the Birendra Kishore Roy Chowdhury Collection. Issue 1 (1st August 2020) - Subramanian, Lakshmi
This article documents attempts to translate a small, eccentric and fragmented personal collection into an act of public history in the form of a small exhibition that showcased some of the most significant components of the collection, in the process addressing the challenges of writing new histories of music, its reception and appreciation, pedagogy and transmission. The rationale for the article is twofold: first, to reflect on the modalities of doing public history and thus generating a broader interest in a slice of Bengal's music history of the late nineteenth and twentieth centuries; and second, to reflect on the possibilities that individual collections such as the Birendra Kishore Roy Chowdhury Collection present for reconceptualizing the emergent field of music studies in India. Yet these concerns also speak to the question of archives and archiving processes in general, to our responsibilities as gatekeepers and users, and to how the very act of archiving a collection gives it a fixity that may be arbitrary.